(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The aim of the study was to improve the results of treatment of patients with purulent cholangitis and mechanical jaundice caused by choledocholithiasis, through the use and treatment, including nasobillar ozone therapy.